Feminist Interpretation of Galatians 3:28 and Its Relevance to Women's Liberation - Tuasela, Juliana Agusthina; Keliwulan, Urbanus (IAKN Ambon, 2023)
The study aims at interpreting Galatians 3:28 from a feminist perspective with relevance in a contemporary context. This study was conducted for some reasons, namely: first, Galatians 3:28 has become the center of controversy, in recent years this text has become increasingly popular from a feminist perspective. In comparison with 1 Corinthians 12:13 and Col.3:11 which record the same idea, this text is considered positive for women and becomes the climax of the biblical statement about gender equality. Second, this text is unique and complex to interpret because it frames the baptismal formula for the new Christianity. Third, Galatians 3:28 is the text that underlies the message of liberation for women in the New Testament. This text forms the basis of fundamental Pauline theology which teaches a spirituality of equality between men and women of all racial and ethnic groups, economic classes, and age groups. This text uses a feminist hermeneutic method, which provides space for women's and men's participation as equal and mutual partners, both privately and publicly. The results of the research show several things, namely: first, Galatians 3:28 is an important verse against equality. Second, this text presents the theological consequences of the legitimacy of the New Testament for universal spiritual equality. Third, this text ensures equal spiritual status and opportunities in leadership for all. In essence, this text is based on equality that has an impact and is relevant to the work of liberation for women.AbstrakStudi bertujuan menafsirkan Galatia 3:28 dari perspektif feminis merelevansikan dalam konteks kontemporer. Studi ini dilakukan dilatari beberapa alasan, yaitu: pertama, Galatia 3:28 menjadi pusat kontroversi, dalam beberapa tahun terakhir maraknya teks ini dari perspektif kaum feminis. Dalam komparasi dengan teks 1 Korintus 12:13 dan Kol.3:11 yang mencatat ide sama, teks ini dianggap positif bagi perempuan dan menjadi klimaks pernyataan alkitabiah tentang kesetaraan gender. Kedua, teks ini unik dan kompleks ditafsirkan karena dibingkai formula pembaptisan untuk Kekristenan baru. Ketiga, Galatia 3:28 merupakan teks yang mendasari pesan pembebasan bagi perempuan dalam Perjanjian Baru. Teks ini menjadi dasar teologi fundamental Pauline yang mengajarkan spiritualitas kesetaraan antara laki-laki dan perempuan dari semua kelompok ras dan etnis, semua kelas ekonomi, dan semua kelompok umur. Teks ini memakai metode hermeneutik feminis, yang memberi ruang partisipasi perempuan dan laki-laki sebagai mitra setara dan mutual secara privat maupun publik. Hasil penelitian menujukkan beberapa hal, yaitu: pertama, Galatia 3:28 adalah ayat penting yang menentang kesetaraan. Kedua, teks ini menyajikan konsekuensi teologis dari legitimasi Perjanjian Baru untuk kesetaraan spiritual universal. Ketiga, teks ini mengafirmasi status spiritual, kesempatan dan kepemimpinan yang sama untuk semua. Intinya, teks ini didasarkan pada kesetaraan yang berdampak dan relevan dengan karya pembebasan bagi perempuan